Dekadents teatrisituatsioonis Oscar Wilde’i „Salomé” näitel - Tanel Lepsoo (Keel ja Kirjandus, 2024)
The article stems from Jean-Paul Sartre’s concept of being in a situation, applied to examine two theatrical situations: the premiere of Oscar Wilde’s one-act tragedy “Salomé” in France, and the stage productions of the play in Estonia before and after World War II. The article demonstrates, in line with other studies, that in the French context, decadence mainly arises from the reluctance of bourgeois intellectuals to acknowledge their class membership and a yearning for the lifestyle of the aristocracy of the intellect, whereas in Estonia, (French) decadence is harnessed for cultural development and lofty aesthetic goals. It is noteworthy that “Salomé” is introduced to Estonian audiences during the building phases of the nation and hence also culture, both in 1919 and 1989. Due to spatial and temporal distance, the play’s sensuality wanes, and eroticism transforms into an exoticism of sorts. The directors find it challenging, and mostly do not aim, to apply the style and techniques characteristic of symbolism in the broader context of a realistic and psychological theatrical tradition. In conclusion, decadence, with its openness to the Other and inherent opposition to utilitarianism and progress, is inherently positive, and its retreat signals society’s stagnation and a pervasive bitterness.